Modern building reuse : documentation, maintenance, recovery and renewal - Riso, Vincenzo (2014)
Index “Foreword” by Vincenzo Riso / The definition of the Field “Two or three things I know about conservation of modern architecture” by Benedetto di Cristina / “Some considerations on the preservation of 20th century architectural heritage” by Teresa Ferreira / “The Architectural Press photographs at the core of the modern architecture paradigms, UK 1950/1970” by Paulo Catrica / “Intervening in modern architecture: a design theme and a research problema” [EN e PT] by José Miguel Rodrigues / “Design as Research in Architecture” [EN e PT] by Pedro Bandeira / “Inspection and condition assessment: Concepts, methods and tools” [EN e PT] by Paulo J. S. Cruz / “Architecture of the 20th century in Seine-Saint-Denis: an emerging heritage” [EN e FR] by Bruno Mengoli / “A conversation on the habitability of the domestic space. The client, the architect, the inhabitant and the house” [EN e PT] by Ana Luísa Rodrigues / “Improving the energy efficiency of existing building envelope” By Peter Erlacher / Marianna Marchesi / “The Tugendhat House between craft tradition and technological innovation. Preservation as sustainable building policy” [EN e PT] by Ivo Hammer / “Cost-effective rehabilitation of the building envelope of a housing development. From diagnosis to completion of the Work” [EN e PT] by Vasco Freitas, Pedro Gonçalves & Sara Stingl de Freitas / “Restoration of Alvar Aalto’s Library in Vyborg” by Maija Kairamo / “Vedute, abstract from «Subtopia: Photography Architecture and the New Towns programme»” by Paulo Catrica